STRATEGI PENINGKATAN LITERASI MEMBACA PADA SISWA SEKOLAH DASAR: SYSTEMATIC LITERATURE REVIEW - Sintia Ramadani; Asep Sahrul Gunawan (STKIP Subang, 2026)
Reading literacy is a fundamental competency that serves as the primary prerequisite for elementary school students' learning success. However, based on PISA 2022 results, the reading literacy level of Indonesian students remains low, particularly in comprehension, inference, and critical thinking. This study aims to identify, analyze, and synthesize effective strategies for improving reading literacy among elementary school students. The method used is a systematic literature review (SLR) following PRISMA guidelines. Data sources consist of 16 scholarly journal articles indexed in SINTA and 1 thesis published between 2016 and 2026. The findings reveal six main strategies: interactive reading (DRTA) increasing mastery from 37% to 87.5%, cooperative learning enhancing engagement, digital literacy, project-based learning increasing mastery from 73% to 93%, illustrated story media, and integrated reading strategies (storytelling, SQ3R). Interactive reading and cooperative learning are the most dominant strategies, significantly enhancing comprehension, engagement, motivation, and critical thinking. Supporting factors include teacher readiness, varied reading materials, parental involvement, positive school climate, and collaboration among teachers, librarians, and counselors. This study concludes that implementing varied, contextual, and sustainable strategies is essential to address low reading literacy. Therefore, it is recommended that teachers apply a combination of interactive and cooperative strategies tailored to students' characteristics, supported by continuous training, strengthening of school libraries, and integration of local wisdom values.